2007
DOI: 10.1108/01425450710776272
|View full text |Cite
|
Sign up to set email alerts
|

On the transferability of “traditional” satisfaction theory to non‐traditional employment relationships: temp agency work satisfaction

Abstract: On the transferability of "traditional" satisfaction theory to non-traditional employment relationships: temp agency work satisfaction Nicole Torka Birgit Schyns Article information:To cite this document: Nicole Torka Birgit Schyns, (2007),"On the transferability of "traditional" satisfaction theory to non-traditional employment relationships: temp agency work satisfaction", Employee Relations, Vol. 29 Iss 5 pp. 440 -457 Permanent link to this document: http://dx.If you would like to write for this, or any oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
1
22
0
2
Order By: Relevance
“…Therefore, user firms' decisions concerning the employment status are not an exclusive predictor of agency workers' attitudes and behaviours, although the overall treatment of non-permanent staff is. In addition, some agency workers voluntarily choose the ‗power of a potential good-bye' (Torka and Schyns 2007). For this group of agency workers, a traditional employment relationship may include undesired outcomes.…”
Section: General Discussion Limitations and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, user firms' decisions concerning the employment status are not an exclusive predictor of agency workers' attitudes and behaviours, although the overall treatment of non-permanent staff is. In addition, some agency workers voluntarily choose the ‗power of a potential good-bye' (Torka and Schyns 2007). For this group of agency workers, a traditional employment relationship may include undesired outcomes.…”
Section: General Discussion Limitations and Consequencesmentioning
confidence: 99%
“…A salient explanation is that there must be a ‗black box' between the labour contract/commitment link: other factors are obscuring a direct relationship. This paper focuses on one of these factors: HRM practices (e.g., Torka and Schyns 2007;Mitlacher 2008).…”
mentioning
confidence: 99%
“…They argue that temporary workers are motivated by different factors than regular employees, because of the absence of an ongoing employer-employee relationship and, in the case of agency workers, because of the triangular relationship between employee, employer and client firm. Torka and Schyns (2007) study satisfaction of temporary agency workers and find that temporary agency workers indeed attach different values to the same job aspects. Furthermore, one might argue that the bundle of characteristics associated with contingent workers' jobs may appeal to them sufficiently to overcome the satisfaction lost from their lack of job security.…”
mentioning
confidence: 98%
“…Torka and Schyns (2007) found that some client organisations influence the pay of agency workers by negotiating with the agency, and that agency workers reward clients' involvement with positive attitudes towards the client. Van Breugel, Olffen and Olie (2005) found that how the agency deals such mundane problems such as payments, contracts, supervisors and coworkers at the agency and the client are effective factors, determining agency support as perceived by the workers.…”
Section: Hrm and Ocwmentioning
confidence: 97%